(untitled) (Religious dialogue and cooperation, 2023)
Coaching is a social phenomenon which transcends the boundaries of a particular profession. Coaching teaches individuals new ways of thinking and how to learn. One of the basic principles of the coaching procedure is self-directed learning. Coaching is dominant in Western culture nowadays since people have recognized that it is a modern need, a prerequisite for their personal and social growth in their lives. Coaching started as Organizational Coaching, as a service offered in organizations. However, it was established as a practice years later, in the 1980s, taking various forms in Education as well. To date, very little empirical research exists on educational coaching for students in High schools, both in Greece and worldwide. Previous studies have used population samples of people of different ages and mainly adult community samples, for example students in higher education and institutions. While hundreds of higher education institutions have implemented coaching programs to help with student success, few coaching programs have been introduced in high schools. Furthermore, most of the literature about coaching at schools shows that coaching for educators has been studied extensively, while the influence coaching can have on students has been underestimated. The main goal of this specific research is to investigate the hypothesis that coaching intervention for final year/ secondary high school students impacts their self-efficacy and personal growth positively. It utilizes a quantitative repeated-measures quasi-experimental design with the use of a questionnaire.